Effect of feeding buttermilk coated diets on growth, carcass characteristics and production cost of crossbred chicken (Bangladesh Journal of Animal Science, 2021)
Growth performance, carcass characteristics and production costs associated with feeding crossbred indigenous chicken on traditional buttermilk coated diets were evaluated. Three batches of day-old Indigenous x Kuroiler crossbred chicks were raised on a commercial diet for one month. At one month, chicken in each of the three batches were weighed and randomly divided into 3 equal groups. Each group comprised of 20 birds. Chicken in each group were either fed coated (dry buttermilk coated maize-bran), combined (buttermilk coated maize bran + commercial diet) or a commercial (control) diet. Average final live weight and feed intake were similar across the three dietary treatments (P>0.05). Feed to gain ratio significantly varied (P0.05) across dietary treatments. On a 5 point hedonic scale, chicken meat produced using coated diets was more acceptable (2.0), compared to combined (2.1) and commercial (3.1) diets (P